Normal reference ranges for cardiac valve cross-sectional areas in preterm infants - Lulu Abushaban; Mariappa Thinakar Vel; Jebaraj Rathinasamy; Prem N Sharma (Wolters Kluwer Medknow Publications, 2018)
Objective : To establish normal reference ranges for cardiac valve crosssectional areas (CSAs) in preterm infants and their correlation with gestational age, body weight, and chronological age. Materials and Methods : In a prospective study, 268 preterm babies fulfilling the criteria for inclusion were examined. Echocardiograms were performed to measure aortic, pulmonary, mitral, and tricuspid valve CSAs on 0-6 day (s) of life and at weekly intervals until they reached 36 weeks. Gestational age was divided into three groups, 24-27, 28-31, and 32-35 weeks, and body weight was divided into five groups, ≤999, 1000-1499, 1500-1999, 2000-2499, and ≥2500 g. Overall group differences were compared for each period of life: 0-6 days and 1-2, 3-4, and ≥5 weeks. Results : The mean gestational age was 29.8 (±2.38 standard deviation [SD]) weeks, ranging between 24 and 35 weeks, and the mean body weight was 1479 (±413 SD) g, ranging between 588 and 3380 g. All cardiac valve CSAs correlated well with body weight. A significant gradual increase was observed in all valve CSAs with body weight during each period of life. Overall, a progressive and significant increase in all valve CSAs was observed during the first 9 weeks of life. Conclusions : Cardiac valve CSAs were found to be significantly correlated with body weight. The study also provides reference data, which can be used as a normal reference tool for valve CSAs in preterm infants against gestational age, body weight, and chronological age.